2001
DOI: 10.1002/chin.200140211
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Structure and Synthesis of Glycoborine, a New Carbazole Alkaloid from the Roots of Glycosmis arborea: A Note on the Structure of Glycozolicine.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…These results are comparable to the results of the reaction executed by us as shown in Scheme 77. The two isomeric tetrahydocarbazoles as reported by theChakravorty groupTo further substantiate our results, a Wolff-Kishner-Huang-Minlon reduction of 258c gave 269c having 1 H-NMR chemical shifts, identical to those reported by the Chakravorty group 119. While the main focus of our group has been to construct the carbazolone ring from 3-(2-nitrophenyl)-2-cyclohexeneone derivatives via the heteroannulation reaction, the concept of initiating an internal nucleophillic addition on the nitro group to form a hydroxycarbazole was a possible consideration.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These results are comparable to the results of the reaction executed by us as shown in Scheme 77. The two isomeric tetrahydocarbazoles as reported by theChakravorty groupTo further substantiate our results, a Wolff-Kishner-Huang-Minlon reduction of 258c gave 269c having 1 H-NMR chemical shifts, identical to those reported by the Chakravorty group 119. While the main focus of our group has been to construct the carbazolone ring from 3-(2-nitrophenyl)-2-cyclohexeneone derivatives via the heteroannulation reaction, the concept of initiating an internal nucleophillic addition on the nitro group to form a hydroxycarbazole was a possible consideration.…”
supporting
confidence: 90%
“…The two isomeric carbazolones, 258c and 258d, obtained via theFischer indole synthesisIn the year 2001, another group of researchers led by A. Chakravorty, a former member of the Chowdhury group, reported a Fischer indole synthesis on the 4methylcyclohexanehydrazone derivative 268, which was prepared in situ from a condensation between m-methoxyphenylhydrazine (267) and 4-methylcyclohexanone (266) 119. The outcome of this reaction was the formation of two isomeric tetrahydrocarbazoles 269c and 269d in a ratio of 9:1 (Scheme 78).…”
mentioning
confidence: 99%
“…For tetrahydrocarbazolones, see: Bringmann et al (1995); Chakravarty et al (2001); Knö lker & Reddy (2002); Lin & Zhang (2000); Matsuo & Ishida (1994); Miki & Hachiken (1993); Scott et al (2006). For biologically active carbazoles, see: Jean et al (2004); Knö lker & Reddy (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…Tetrahydrocarbazolones have been used extensively as advanced intermediates in synthetic efforts toward a number of naturally occurring carbazole alkaloids (Bringmann et al, (1995); Chakravarty et al, (2001); Knölker & Reddy (2002);Lin & Zhang 2000; Matsuo & Ishida (1994); Miki & Hachiken (1993); Scott et al, (2006)). Jean et al (2004) andKnölker & Reddy 2008 Thomas Gunaseelan et al (2009), Sridharan et al (2008) and Thiruvalluvar et al (2007) have reported the crystal structures of substituted carbazole derivatives, in which the carbazole units are not planar.…”
Section: S1 Commentmentioning
confidence: 99%
“…In 1992, Bhattacharyya et al isolated glycozolicine ( 2 ) from the roots of Glycosmis pentaphylla 6. Initially, the structure of glycozolicine ( 2 ) had been incorrectly assigned as 5‐methoxy‐3‐methylcarbazole, but in 2001, Chakravarty et al reassigned its structure as 8‐methoxy‐3‐methylcarbazole ( 2 ) on the basis of the total syntheses of both isomeric compounds and the comparison of spectroscopic data with those of the natural product 7. Mukoline ( 3 ) and mukolidine ( 4 ) were obtained in 1982 by Chakraborty and co‐workers from the benzene extract of the roots of Murraya koenigii Spreng.…”
Section: Introductionmentioning
confidence: 99%